Effect of Tissue Composition and Microstructure on Rabbit Meat Optical Properties. Issue 6 (June 2023) - Hao, Yuan; Li, Congyan; Li, Fanglin; Liu, Cailing; Wang, Hongying; Xie, Xiaohong
To facilitate the design of an optical detection system for assessing rabbit meat quality, nine rabbits of different ages, weights, and varieties were used to collect optical coefficients, compositions, and microstructures from external oblique muscle (EOM) and internal oblique muscle (IOM) samples to research the relationship between them. The results show that rabbit age had a significant influence ( P  < 0.05) on the absorption coefficient (μa ) and the proportion of myoglobin in IOM and EOM, and the older the rabbits are, the greater the μa and the proportion of myoglobin are. Weight also significantly ( P  < 0.05) influenced the muscle fiber cross-sectional area. The age and weight had a significant ( P  < 0.05) impact on the reduced scattering coefficient (μs ′). The linear fitting results between the relative proportion of myoglobin and the μa showed that the higher the myoglobin content is, the greater the μa is. The linear fitting results between the cross-sectional area of muscle fiber and the μs ′ showed that the smaller the cross-sectional area of muscle fiber is, the greater the μs ′ is. These results will be helpful to intuitively understand the working principle of spectral technology in meat quality detection. Graphical Abstract This is a visual representation of the abstract.